Abundance and species richness of fish associated to Thalassia testudinum at Cariaco Gulf, Venezuela. - Allen Peña, Thays (2004)
Fish are among the most abundant and diverse groups in Thalassia testudinum communities, in turn considered among the most productive and important ecosystems in marine environments. Three stations were sampled in the southern shore of Cariaco gulf (northwestern Venezuela) to quantify fish associated with T. testudinum, from December 1996 to November 1997. We used a 50 m long beach net (“chinchorro playero”, height 1.50 m, mesh opening 0.7 cm. A total of 15 509 individuals were collected: 27 families, 38 genera and 44 specie were identified. The most abundant, in descending order, were Haemulon boschmae, Nicholsina usta, Orthopristis ruber, Xenomelaniris brasiliensis and Diplodus argenteus. Thirty three species were occasional visitors (75.0%) and ten were recurrent visitors (22.7%). The permanent resident, N. usta, is a characteristic species that uses T. testudinum throughout its life cycle.